(untitled) - Orszag, Miguel (New York, 2008)
In this second edition, there is an enlarged chapter on decoherence, as well as additional material dealing with elements of quantum computation, entanglement of pure and mixed states as well as a chapter on quantum copying and processors. These topics are presented in a unified and didactic manner. The presentation of the book is clear and pedagogical.
Quang lượng tử
Keywords: Quantum optics,Quang học lượng tử